2023
DOI: 10.1007/s00264-023-05714-z
|View full text |Cite
|
Sign up to set email alerts
|

Dithiotreitol pre-treatment of synovial fluid samples improves microbiological counts in peri-prosthetic joint infection

Abstract: Purpose Synovial fluid cultures of periprosthetic joint infections (PJI) may be limited by bacteria living in the fluids as biofilm-aggregates. The antibiofilm pre-treatment of synovial fluids with dithiotreitol (DTT) could improve bacterial counts and microbiological early stage diagnosis in patients with suspected PJI. Methods Synovial fluids collected from 57 subjects, affected by painful total hip or knee replacement, were divided into two aliquots, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Arthrocentesis can show whether a joint effusion is inflammatory or not, but microbiological confirmation is needed to rule out or identify an infection. Recent reports have linked the resistance of bacterial joint infections to standard therapies to the presence of bacteria and biofilm aggregates floating in the SF [ 7 , 21 , 22 ]. With reported sensitivities as low as 45% [ 23 ], the poor efficacy of existing microbiological tests on SF may be explained by the ability of bacteria to reside in biofilm aggregates.…”
Section: Synovial Fluid (Sf)mentioning
confidence: 99%
See 4 more Smart Citations
“…Arthrocentesis can show whether a joint effusion is inflammatory or not, but microbiological confirmation is needed to rule out or identify an infection. Recent reports have linked the resistance of bacterial joint infections to standard therapies to the presence of bacteria and biofilm aggregates floating in the SF [ 7 , 21 , 22 ]. With reported sensitivities as low as 45% [ 23 ], the poor efficacy of existing microbiological tests on SF may be explained by the ability of bacteria to reside in biofilm aggregates.…”
Section: Synovial Fluid (Sf)mentioning
confidence: 99%
“…In a recent work by Drago et al [ 7 ], it was shown that the ability of bacteria to live in aggregates in the SF may be a common behavior among several if not all bacteria. They collected SF from 57 subjects affected by a painful total hip or knee replacement, with suspicions of a PJI; then, the samples were divided into two aliquots, one pretreated with dithiothreitol (DTT), and one with normal saline.…”
Section: Synovial Fluid (Sf)mentioning
confidence: 99%
See 3 more Smart Citations